Summary of effects of parental smoking on the respiratory health of children and implications for research. Issue 4 (1st April 1999) - Cook, Derek G; Strachan, David P
Abstract : BACKGROUND: Two recent reviews have assessed the effect of parental smoking on respiratory disease in children. METHODS: The results of the systematic quantitative review published as a series in Thorax are summarised and brought up to date by considering papers appearing on Embase or Medline up to June 1998. The findings are compared with those of the review published recently by the Californian Environmental Protection Agency (EPA). Areas requiring further research are identified. RESULTS: Overall there is a very consistent picture with odds ratios for respiratory illnesses and symptoms and middle ear disease of between 1.2 and 1.6 for either parent smoking, the odds usually being higher in pre-school than in school aged children. For sudden infant death syndrome the odds ratio for maternal smoking is about 2. Significant effects from paternal smoking suggest a role for postnatal exposure to environmental tobacco smoke. Recent publications do not lead us to alter the conclusions of our earlier reviews. While essentially narrative rather than systematic and quantitative, the findings of the Californian EPA review are broadly similar. In addition they have reviewed studies of the effects of environmental tobacco smoke on children with cystic fibrosis and conclude from the limited evidence that there is a strong case for a relationship between parental smoking and admissions to hospital. They also review data from adults of the effects of acute exposure to environmental tobacco smoke under laboratory conditions which suggest acute effects on spirometric parameters rather than on bronchial hyperresponsiveness. It seems likely that such effects are also present in children. CONCLUSIONS: Substantial benefits to children would arise if parents stopped smoking after birth, even if the mother smoked during pregnancy. Policies need to be developed which reduce smoking amongst parents and protect infants and young children from exposure to environmental tobacco smoke. The weight of evidence is such that new prevalence studies are no longer justified. What are needed are studies which allow comparison of the effects of critical periods of exposure to cigarette smoke, particularly in utero, early infancy, and later childhood. Where longitudinal studies are carried out they should be analysed to look at the way in which changes in exposure are related to changes in outcome. Better still would be studies demonstrating reversibility of adverse effects, especially in asthmatic subjects or children with cystic fibrosis.